2010
DOI: 10.1108/17506141011074138
|View full text |Cite
|
Sign up to set email alerts
|

Are “standardized performance appraisal practices” really preferred? A case study in China

Abstract: PurposeIn spite of the increasing awareness that standardized performance appraisal practices must fit in varied local contexts, limited research and mixed findings still cloud our understanding about how those appraisal practices are perceived and implemented in the subsidiaries of multinational corporations (MNCs). The purpose of this paper is to examine this issue, aiming to clarify the contextual and cultural boundary of standardized appraisal practices in China.Design/methodology/approachA case study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 36 publications
2
22
0
1
Order By: Relevance
“…Given current circumstances organizations are paying particular attention to one specific HRM practice that influences an organizations' performance which is performance appraisal (Chen & Eldridge, 2010). Even though performance appraisals are considered a necessity, both appraisers and appraises dread the entire process (Lim & Ling, 2012).…”
Section: Performance Appraisalsmentioning
confidence: 99%
“…Given current circumstances organizations are paying particular attention to one specific HRM practice that influences an organizations' performance which is performance appraisal (Chen & Eldridge, 2010). Even though performance appraisals are considered a necessity, both appraisers and appraises dread the entire process (Lim & Ling, 2012).…”
Section: Performance Appraisalsmentioning
confidence: 99%
“…These perceptions affect their behaviour in the organisation, ultimately influencing the attainment of the strategic goals of the organisation. The literature review revealed that the appraisal process is related to the social environment under which the employee operates (Zheng et al, 2012;Marjani & Ardahaey, 2012), and that the system in place cannot be blamed if there is no management commitment to make the process work (Chen & Eldridge, 2010). Without set objectives, employees have no clear direction as to what to achieve, which makes the appraisal process biased, creating negative perceptions of the process (Ikramullah et al, 2011).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The study also verifies the research by Ikramullah et al (2011), St-Onge, Morin, Bellehumeur & Dupius (2009), and Tuytens and Devos (2012, in that employee justice perceptions relating to performance management practices may be explained using organisational justice theories according to the four justice dimensions of procedural, distributive, interactional and informational justice. If employees are more motivated when they perceive their performance appraisals as fair and trustworthy (Froydis, Marnburg & Furunes, 2010;Chen & Eldridge, 2010;Davila & Elvira, 2009;Day, 2011) then ensuring the processes and ensuring that the outcomes from the process are seen as fair can lead to improved organisational performance (Ikramullah et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations